The Crisis and Italian Families - Secondulfo, Domenico; Tronca, Luigi (Italian Sociological Review, 2016)
In this article the issue of the effects of the economic crisis on consumption in Italy is discussed. In particular, the authors present some information about the strategies of consumption in Italy, from a part of the data collected during some of the research conducted by the Observatory on the consumption of families (University of Verona, Italy). The data analyzed were collected through several surveys conducted in the five years between 2009 and 2013. After presenting some data on the economic status of the families of respondents, the authors discuss, among other things, the issue of the request for financial help – showing how the primary networks are increasingly over-stressed – and the growth of the incidence of households that reduce their spending in various areas of commodities – which show that the most significant growth appears to medicines and products for personal care and toiletries, and food. Finally, the changes, over time, of the incidence of some general profiles of consumers are shown.